1996
DOI: 10.1016/0014-5793(96)00293-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of angiotensins by head membranes of the leech Theromyzon tessulatum

Abstract: Angiotensins (angiotensin I, angiotensin II, angiotensin II-amide) have been isolated in leeches and such peptides are involved in diuresis in these animals. To explore possible inactivation mechanisms of these peptides, angiotensins were incubated with head membranes of the leech T. tessulatum. Membranes derived from head parts of this leech are very rich in peptidases. They contain endopeptidase-24.11-1ike enzyme (NEP-like) associated with a battery of exopeptidase. The way that angiotensins are degraded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…These data are in line with previous studies demonstrating that LORF level increased at stage 3 corresponding to a high water retention in the animal and gametogenesis [19]. Similarly, ACE as well as angiotensin II levels decrease at this stage of the animal [26,32,33]. These data show that yolk proteins are a natural source of ACE inhibitors in invertebrates; ovohemerythrin is a potential source of LORF [34] and ACE is implicated in the modulation of the reproduction.…”
Section: Resultssupporting
confidence: 91%
“…These data are in line with previous studies demonstrating that LORF level increased at stage 3 corresponding to a high water retention in the animal and gametogenesis [19]. Similarly, ACE as well as angiotensin II levels decrease at this stage of the animal [26,32,33]. These data show that yolk proteins are a natural source of ACE inhibitors in invertebrates; ovohemerythrin is a potential source of LORF [34] and ACE is implicated in the modulation of the reproduction.…”
Section: Resultssupporting
confidence: 91%
“…Biosynthesis study of leech AII revealed the existence of a renin- [22] and angiotensin-converting like [23][24][25] enzymes as well as the enzyme implicated in its catabolism [ Fig. 1, 25].…”
Section: Angiotensin-like Peptidesmentioning
confidence: 99%
“…This posttranslational step involves many types of enzymes that have been identified both in vertebrates and in invertebrates. Between these enzymes, neutral endopeptidase (NEP) [19,50,51], ACE [23][24][25], renin [22], aminopeptidases [52], and serine proteases belonging to the subtilisin family [45] play an important role in neuropeptide precursors processing.…”
Section: Are Neuropeptide Processing Enzymes Present In Invertebrates?mentioning
confidence: 99%
See 1 more Smart Citation
“…NEP-like proteins have been identified in bacteria, archaea and the animal kingdom, and are more diverse in invertebrates (see entries under M13 family in the MEROPS database; http:// merops.sanger.ac.uk) [12]. NEP-like activity which is inhibited by phosphoramidon, a potent inhibitor of human NEP, has been identified in molluscs [13,14], a nematode [15], an annelid [16] and several insect species, including the house fly (Musca domestica) [17], fruit fly (Drosophila melanogaster) [18,19], the gypsy moth (Lymantria dispar) [20], the tomato moth (Lacanobia oleracea) [19], two locust species (Schistocerca gregaria [21] and Locusta migratoria [19]) and a cockroach (Leucopheae maderae) [19,22]. NEP-like activity is enriched in synaptic membranes prepared from the locust central nervous system [21], and has been shown histochemically to be present in neuropil regions of the cockroach and locust brain [22].…”
Section: Introductionmentioning
confidence: 99%